Peces migratorios al interior de una central hidroeléctrica: caso Miel I, cuenca del río Magdalena (Caldas-Antioquia), Colombia (2014)
One of the most obvious impacts of damming a river is the disruption of migratory routes, however, the characteristics of the dam, the river and its fish fauna make impossible the generalizations about the possible effects. Since the beginning of the operation of La Miel I hydropower plant, it was detected the entrance of fish into the hydropower plant (through the surge chamber) from La Miel river. To determine the composition of the fish and evaluate the potential effects on migration, for one year (April 2010-April 2011) adult individuals were tagged and released and ichthyoplankton collections were made, both in the surge chamber and in the discharge channel. Individuals of migratory and non-migratory species, mainly piscivorous and detritus-scrapers were found. Individuals who entered the surge chamber were able to find quickly the exit through the restriction orifice and returned to the main channel of La Miel River. The fish did not spawn in the central structures. We conclude that the surge chamber is not an absolute barrier to migration, but it is a staging habitat for migrant individuals.